1984
DOI: 10.1007/bf00495401
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type changes in rat skeletal muscle after intense interval training

Abstract: Female Sprague-Dawley rats were subjected to a ten week training program to determine the influence of intense interval running on the fiber type composition of selected hindlimb muscles; soleus (S), plantaris (P), deep vastus lateralis (DVL), and superficial vastus lateralis (SVL). The muscles of one hindlimb were used for histochemical ATPase analysis to determine the distribution of fiber types and those of the contralateral hindlimb were assayed biochemically for citrate synthase activity (an aerobic marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 32 publications
3
16
0
3
Order By: Relevance
“…Approximately half (52.8%) of the ®bres expressing MHCd also reacted positively for MHCf and MHCs, whereas 27.6% reacted with only the MHCf, and 17.8% with only the MHCs. The remaining 1.8% of MHCd + ®bres did not react for the presence of adult The adult ®bre type distribution of all S muscles was similar to that previously reported for this muscle (Ho et al 1983;Armstrong and Phelps 1984;Luginbuhl et al 1984), with 79.3% of ®bres reacting for MHCs, 12.2% for MHCf, and 6.9% reacting for both adult MHCs and MHCf isoforms.…”
Section: Co-expression Of Mhc Isoforms Within ®Bressupporting
confidence: 85%
“…Approximately half (52.8%) of the ®bres expressing MHCd also reacted positively for MHCf and MHCs, whereas 27.6% reacted with only the MHCf, and 17.8% with only the MHCs. The remaining 1.8% of MHCd + ®bres did not react for the presence of adult The adult ®bre type distribution of all S muscles was similar to that previously reported for this muscle (Ho et al 1983;Armstrong and Phelps 1984;Luginbuhl et al 1984), with 79.3% of ®bres reacting for MHCs, 12.2% for MHCf, and 6.9% reacting for both adult MHCs and MHCf isoforms.…”
Section: Co-expression Of Mhc Isoforms Within ®Bressupporting
confidence: 85%
“…The statistically significant shift from type II to type I fibers and from subtype liB to subtype IIA fibers in the two heads of the triceps brachii muscle of the runners served as a positive control (a prime mover muscle) for the multifidus muscles. The response of these muscles is consistent with earlier reports on the effects of endurance training on muscle fibers [19,20,27,29].…”
Section: Discussionsupporting
confidence: 91%
“…However, in the present study exercise training did not increase the percentage of type I fibers, possibly because the training duration or intensity advocated in the present study was not enough to induce a muscle fiber type transition in SHR. On the other hand, it has been shown that, even when an exercise-induced fiber type transition from type II to type I does not take place in soleus muscle, it occurs in other skeletal muscles [27]. Thus, we cannot exclude the possibility that fiber type transition in skeletal muscles other than soleus muscle contributed to the improved exercise capacity in EX.…”
Section: Discussionmentioning
confidence: 85%